Validity and Reliability of Critical Care Family Needs Inventory (CCFNI) in Indonesian Version - Wantiyah Wantiyah; Muhamad Zulfatul A'la; Baskoro Setioputro; Siswoyo Siswoyo (NurseLine Journal, 2018)
Family-centered care (FCC) in intensive care as a family-based care approach has been developed for a long time, but this development in Indonesia is still not optimally created. The FCC needs basic data about the needs of the family who are caring for it, so the need for the family can be identified therefore nursing intervention can be done optimally. One measure that has been developed to assess family needs is Critical Care Family Needs Inventory (CCFNI). The purpose of this study was to analyze the CCFNI questionnaire in Indonesian version. This study tried to test the questionnaire through several steps translation into Indonesian, validity testing in the form of validity content documents (CVI) and construct validity and reliability testing. The results of the CVI test on 45 Indonesian language CCFNI questionnaire statements found that the CVI value was in the range 0.6-0.9 obtained 36 valid statement items, while the results of the construct validity test were found to be valid. Reliability test results obtained an alpha value of 0.97 which means it is very reliable. The conclusion is that the Indonesian version of the CCFNI questionnaire which is translated into Kebutuhan Keluarga Pasien di Ruang Perawatan Intensif (K3PI) is valid and reliable.